2018
DOI: 10.1103/physrevapplied.10.064056
|View full text |Cite
|
Sign up to set email alerts
|

Electric Noise Spectra of a Near-Surface Nitrogen-Vacancy Center in Diamond with a Protective Layer

Abstract: Surface noise is a detrimental issue for sensing devices based on shallow nitrogen vacancy (NV) color center diamonds. A recent experiment indicates that electric field noise is significant compared to magnetic field noise. They also found that the electric field noise can be reduced with a protective surface layer, though the mechanism of noise reduction is not well understood. We examine the effect of a protective surface layer on the noise spectrum, which is caused by surface charge fluctuations. We use the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…By mapping out a diamond's spin-bath spectral noise profile, tailored sensing protocols can be designed to more efficiently extract target signals. To this end, dynamical decoupling sequences, such as those in the CPMG and XY families, are employed for noise mapping (Bar-Gill et al, 2012Romach et al, 2015;Chrostoski, Sadeghpour, and Santamore, 2018;Bauch et al, 2019). By varying both the total precession time and the number of refocusing pulses, noise at a variable target frequency can be isolated, ultimately allowing measurement of the entire spin-bath spectral noise profile.…”
Section: A Dynamical Decoupling For Ac Magnetometrymentioning
confidence: 99%
“…By mapping out a diamond's spin-bath spectral noise profile, tailored sensing protocols can be designed to more efficiently extract target signals. To this end, dynamical decoupling sequences, such as those in the CPMG and XY families, are employed for noise mapping (Bar-Gill et al, 2012Romach et al, 2015;Chrostoski, Sadeghpour, and Santamore, 2018;Bauch et al, 2019). By varying both the total precession time and the number of refocusing pulses, noise at a variable target frequency can be isolated, ultimately allowing measurement of the entire spin-bath spectral noise profile.…”
Section: A Dynamical Decoupling For Ac Magnetometrymentioning
confidence: 99%
“…Our prediction method can be used to systematically optimize the design and fabrication of future trappedion setups, as the electrode geometry and materialsincluding contaminant or oxide layers -can be adjusted in the FEA simulations to suppress heating effects due to dielectrics. Finally, we note that these results are also relevant for devices such as nitrogen-vacancy centers [40,41] and donor spins in silicon [42] that are disturbed by environmental noise due to nearby surfaces.…”
mentioning
confidence: 73%
“…In some crystals used for optical device applications, crystal field splitting can produce Fano noise from charge fluctuations that contributes to the electric field noise [23,24,25]. In previous work we studied the electric field noise and found that surface electric field noise comes from surface charge fluctuations where the surface covering layer is the key to controlling this type of noise [26].…”
Section: Introductionmentioning
confidence: 98%